Voting over Selective Immigration Policies with Immigration Aversion - Giuseppe Russo (Economics and Econometrics Research Institute (EERI), 2008)
The claim that "skilled immigration is welcome" is often associated to the increasing adoption of selective immigration policies. I study the voting over differentiated immigration policies in a two-country, three-factor one-period model where there exist skilled and unskilled workers, migration decisions are endogenous, enforcing immigration restriction is costly, and natives dislike unskilled immigration. According to my findings, decisions over border closure are made to protect the median voter when her capital endowment is sufficiently small. Therefore I argue that the professed favour for skilled immigration veils the protection for the insiders. This result is confirmed by the observation that entry is rationed for both skilled and unskilled workers. Moreover, immigration aversion helps to explain the existence of entry barriers for unskilled workers in countries where the majority of voters is skilled.
Keywords: D72; F22; J18; 330; Selective immigration policies; multidimensional voting; Condorcet winner